2017
DOI: 10.1098/rsta.2016.0077
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds number trend of hierarchies and scale interactions in turbulent boundary layers

Abstract: Small-scale velocity fluctuations in turbulent boundary layers are often coupled with the larger-scale motions. Studying the nature and extent of this scale interaction allows for a statistically representative description of the small scales over a time scale of the larger, coherent scales. In this study, we consider temporal data from hot-wire anemometry at Reynolds numbers ranging from Re τ ≈2800 to 22 800, in order to reveal how the scale inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
119
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(134 citation statements)
references
References 53 publications
14
119
1
Order By: Relevance
“…More qualitatively, we comment that the UMZ/VF flow structure analysed here may constitute a 'straight' section of a longer superstructure that slowly meanders in the streamwise direction, and that the coupling mechanisms elucidated herein have the potential both to complement those described by the modelling framework of Sharma et al [35] and to connect to the features observed in the numerical and physical experiments of Cossu & Hwang [36] and Baars et al [37], respectively. In contrast to the recent work by Hwang et al [11,12,16] discussed in §1, this study captures only a single interacting UMZ/VF 'unit'.…”
Section: Resultsmentioning
confidence: 89%
“…More qualitatively, we comment that the UMZ/VF flow structure analysed here may constitute a 'straight' section of a longer superstructure that slowly meanders in the streamwise direction, and that the coupling mechanisms elucidated herein have the potential both to complement those described by the modelling framework of Sharma et al [35] and to connect to the features observed in the numerical and physical experiments of Cossu & Hwang [36] and Baars et al [37], respectively. In contrast to the recent work by Hwang et al [11,12,16] discussed in §1, this study captures only a single interacting UMZ/VF 'unit'.…”
Section: Resultsmentioning
confidence: 89%
“…Although the spectral expression of the reconstruction operator discussed in the previous section is very useful in understanding the behaviour of the different flow scales, its physical-space counterpart defined in (8) and (9) gives a more intuitive representation of the operation that is actually being performed. It is probably also easier to generalise to wall-bounded flows besides the channel.…”
Section: B Reconstruction In Physical Spacementioning
confidence: 99%
“…This paper focuses on the properties of the estimations of logarithmic-layer turbulence using noiseless, although potentially incomplete, wall measurements from DNS. The widespread availability of data in the last years has allowed various research groups to test the performance of similar methods with considerable success [7][8][9][10][11]. These works differ from ours in that most of them focus on the use of physically motivated linear models [9,10] to relate velocity measurements at one y to predict the same velocity component at another wall-normal distance.…”
mentioning
confidence: 98%
“…It is instructive to present an energy spectrogram: premultiplied spectra at 40 logarithmically-spaced positions within the range 10.6 z + δ + are presented with iso-contours of k + x φ + uu in Figure 1(a). These spectra were obtained from hot-wire measurements at Re τ ≈ 14 100 in Melbourne's TBL facility (Baars et al 2017a). Near-wall streaks (Kline et al 1967) dominate the inner-spectral peak in the TBL spectrogram (identified with the × marker at λ + x = 10 3 and z + = 15), while large-scale organized motions cause a broad spectral peak in the log-region, indicated with a × marker at λ x = 4δ and z + = 3.9Re 1 /2 τ ≈ 464 (Mathis et al 2009).…”
Section: Introduction and Contextmentioning
confidence: 99%